Reliability of a New Clinical Instrument for Measuring Internal and External Glenohumeral Rotation - Lindenfeld, Thomas N. (Sports Health, 2015)
BACKGROUND: The shoulder plays a critical role in many overhead athletic activities. Several studies have shown alterations in shoulder range of motion (ROM) in the dominant shoulder of overhead athletes and correlation with significantly increased risk of injury to the shoulder and elbow. The purpose of this study was to measure isolated glenohumeral joint internal/external rotation (IR/ER) to determine inter- and intraobserver reliability of a new clinical device. HYPOTHESIS: (1) Inter- and intraobserver reliability would exceed 90% for measures of glenohumeral joint IR, ER, and total arc of motion; (2) the dominant arm would exhibit significantly increased ER, significantly decreased IR, and no difference in total arc of motion compared with the nondominant shoulder; and (3) a significant difference exists in total arc between male and female patients. STUDY DESIGN: Case series. LEVEL OF EVIDENCE: Level 4. METHODS: Thirty-seven subjects (mean age, 23 years; range, 13-54 years) were tested by 2 orthopaedic surgeons. A single test consisted of 1 arc of motion from neutral to external rotation to internal rotation and back to neutral within preset torque limits. Each examiner performed 3 tests on the dominant and nondominant shoulders. Each examiner completed 2 installations. RESULTS: Testing reliability demonstrated that neither trial, installation, nor observer were significant sources of variation. The maximum standard deviation was 1.3° for total arc of motion and less than 2° for most other measurements. Dominant arm ER was significantly greater than nondominant arm ER (P = 0.02), and dominant arm IR was significantly less than nondominant arm IR (P = 0.00). Mean total rotation was 162°, with no significant differences in total rotation between dominant and nondominant arms (P = 0.34). Mean total arc of motion was 45° greater in female subjects. Differences in total arc of motion between male and female subjects was statistically significant (P < 0.00). CONCLUSION: This simple, clinical device allows for both inter- and intraobserver reliability measurements of glenohumeral internal and external rotation.